Diseño de un sistema de gestión de calidad para la escuela particular Pío XII, ubicada en el sector sur del Distrito Metropolitano de Quito - Haro Haro, Edwin Ramiro (2014)
The present investigation was to develop a system of quality management for Pio XII Private School. The first chapter analyzes the theoretical foundation on quality management systems, internal regulations and manuals of procedures. In chapter two a diagnosis of the current situation of the institution is made. For such diagnosis a SWOT analysis was made, using information gathering techniques such as surveys and interviews with students, faculty and administrative staff. With this information flowcharts of existing processes were performed. The third chapter presentsthe system’s proposal based on the 9001 – 2008ISO. Within this proposal the internal labor regulations are developed, to finally present the organization’s procedures manual. In chapter four the presentation of the system as well as the conclusions and recommendations are made.